Optical study of ethanol gasoline blends with or without heating - Abdul Hadi, Abd Majid (2010)
This thesis deals with optical study of ethanol gasoline blends with or without heating. The aim of this research is to study about spray atomization characteristics of ethanol blended gasoline fuel as well as pure gasoline in a direct injection gasoline injector of a gasoline engine. Spray characteristics including spray angle, spray tip penetration and spray width. Investigation of the spray characteristics of different ratio of gasohol fuel blends using optical measurement. Then analysis qualitative result from experimental. The scopes of this research are choosing specific fuel injector and optical measurement, setup test rig for experimental using high pressure chamber and choosing fuel blends as a sample to doing experimental. Choosing fuel blends E0 and E10 as a sample to doing experimental. Spray characteristics that focus only on spray angle and spray tip penetration. After test rig fabrication is done and all equipment has been setup, experiment is done by supplying pressure at 4 bar from high pressure pump to fuel injector that attach to high pressure chamber. Ambient temperature was set to 300 K and ambient pressure is 0.1 MPa. While injector is spray a video imaging recording and result was display according to time frame. Video imaging has been analyzed and result is compared according spray evolution by time.